The Sydney Modified Alberta Reconstruction Technique (SM-ART) for dental rehabilitation following mandibulectomy or maxillectomy. Issue 5 (May 2021) - Johal, M.; Leinkram, D.; Wallace, C.; Clark, J.R.
Abstract: The Sydney Modification of the Alberta Mandibular Reconstruction technique (SM-ART) is a hybrid of the Rohner method and the Alberta Reconstructive Technique (ART). SM-ART differs from ART in three ways, notably the use of custom plates, intraoral placement of implants via three-dimensionally printed guides and a skin graft buried deep into the skin paddle of the fibula flap in the first stage of the reconstruction.